Fluxus : Fluxus International & C°. - Vautier, Ben (Liège : Musée Saint-Georges, 1980)
Brecht, George ; Chiari, Giuseppe ; Schmit, Tomas ; Flynt, Henry ; Vautier, Ben ; Maciunas, George ; Poinsot, Jean Marc ; Vostell, Wofl ; Beuys, Joseph ; Brecht, George ; Des Grand Parents ; etc.
This catalogue is not finished. Every now and then a new chapter and information will be added. We never hope to finish this catalogue. Fluxus is incomplete.
Frans & Engels
boek